Learning To Draw Natural Objects In The Independent Learning Curriculum At Smpn 2 Semarang - Johan Sutarjo (Journal Of Social Science (JoSS), 2023)
Based on the results of research on "Learning to Draw Natural Objects in the Independent Learning Curriculum at SMPN 2 Semarang" at SMPN 2 Semarang in the 2022/2023 academic year, especially in Semarang City, they will start conducting a teaching and learning activity which is carried out offline in line with the rules set by Ministry of Education and Culture of the Republic of Indonesia. This independent learning curriculum is also applied to SMP Negeri 2 Semarang for new students in grade 7. This research is in a field location at SMP Negeri 2 Semarang where the school is located on Jl. Brigadier General Katamso No. 14, Karangtempel, Kec. Semarang Tim., Semarang City, Central Java 50242. The location of the research was determined because this school is one of the best schools in the city of Semarang. The purpose of this study was specifically formulated: To find out and explain learning to draw natural objects in the Free Learning Curriculum at SMPN 2 Semarang, To find out and explain the driving factors for learning to draw natural objects in the Free Learning Curriculum at SMPN 2 Semarang, and To find out and explain the factors obstacles to learning to draw natural objects in the Independent Learning Curriculum at SMPN 2 Semarang. This research has used a descriptive study, namely research that has the aim of describing a situation. This research approach uses a qualitative approach because it examines information, information, & symptoms from an observation process during this research regarding "Learning to Draw Natural Objects in the Independent Learning Curriculum at SMPN 2 Semarang". This research has carried out data collection techniques in several ways, namely observation, documentation, interviews, and questionnaires.